JATROPHA PRODUCTION IN FUNCTION OF ORGANIC FERTILIZATION WITH CASSAVA WATER AND COW URINE (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The objective of this study was to evaluate the production of jatropha (Jatropha curcas L.) submitted to fertilization with cow urine and cassava water. The experiment was conducted under field conditions in the municipality of Lagoa Seca, Paraíba State, Brazil. A 5 x 5 factorial scheme was used in a randomized complete block design with 25 treatments and 4 replicates, using different volumes of cow urine and cassava water. Irrigation was performed twice a week corresponding to 100% of ET0, where all plants received the same water blade. The syrup with 750 mL of cassava water and 750 mL of cow urine provided a greater number of fruits (33.00); however, the larger green mass of the fruits (224.59 g) was obtained when cow urine was added into 1,000 mL of cassava water. The dry weight of the fruits obtained the lowest value (48.92 g), when 250 mL of cow urine was used in the absence of cassava water. The cow urine and cassava water increase production and weight of the fruit of jatropha, which can be used as organic fertilizer for the crop.